Success rates of pediatric dental referrals made by public health dental hygiene practitioners. (19th November 2020) - Burgette, Jacqueline M.; Mestre, Yanelis; Martin, Brian; Ray, Kristin N.; Stiles, Amy; Hoberman, Alejandro
Abstract: Objectives: The purpose of this study was to evaluate whether Public Health Dental Hygiene Practitioner (PHDHP) referrals to pediatric dentists were more successful for children younger than 3 years old and those with dental caries. Methods: We reviewed the electronic health records of 1, 450 children, age 1 to 12 years, who completed a dental visit with a PHDHP in 2017 at UPMC Children's Hospital of Pittsburgh's (CHP) Primary Care Center. We tracked whether children who visited the onsite PHDHP accepted a referral to CHP pediatric dentists, and if so, whether they successfully completed the referral. Results: Of the 1, 450 children who visited the PHDHP, 67 percent ( n = 973) accepted a referral to CHP pediatric dentists. Of these referrals, 32 percent (312/973) were successfully fulfilled. The proportions of accepted and fulfilled referrals were significantly higher for children older than 3 years old and those with dental caries. After controlling for child age, gender, and insurance status, children with dental caries had 5.7 times greater odds of successful referral from the PHDHP to the pediatric dentist compared to children without dental caries (95 percent CI 4.1–7.9). Conclusions: PHDHPs were more successful referring children older than 3 years old and those with dental caries to pediatric dentists. PHDHPs are allied dental health professionals that can be effective at referring children to pediatric dentists when they have dental caries. Additional strategies are needed to enhance the success rate of dental referrals for young children under 3 years old.